Bingo Game in Improving Dental Health Knowledge in Elementary School - Octavianita, Dahlia; Purnama, Tedi; Emini, Emini; Nurilawaty, Vitri (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: Effective education outreach is influenced by the media and methods used. Educating elementary school students requires methods that can capture their attention, such as using gaming media. With the advancement of technology, there are many interactive games that can be developed for use as educational tools. One interactive gaming medium that can be used for education outreach in this context is bingo. Modifying bingo into an educational medium can cultivate teamwork among students, enhance student engagement in learning, and create a more vibrant learning atmosphere. Objective: To analyze the level of dental health knowledge of 5th grade students at SDN Beji 2 Depok before and after education using the bingo game.  Method: This research employs a quasi-experimental method with a one-group pretest-posttest design. It was conducted at SDN Beji 2 Depok, utilizing total sampling, involving 47 students. The independent variable is the bingo game, and the dependent variable is the level of dental health knowledge among students. The instruments used include a questionnaire and the bingo game media. Data analysis is conducted using the Wilcoxon signed-rank test. Results: This study shows the average value of dental health knowledge before playing with bingo games is 65.53 and after playing with bingo games is 93.62, with Wilcoxon test results of p<0.001. Conclusion: Bingo game is effective in improving dental health knowledge among elementary school students.